2021
DOI: 10.15403/jgld-3345
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib as First-line Treatment of Hepatocellular Carcinoma in Patients with Impaired Liver Function in Advanced Liver Cirrhosis: Real World Data and Experience of a Tertiary Hepatobiliary Center

Abstract: Background and Aims: Lenvatinib is a multikinase inhibitor approved for systemic first line treatment of hepatocellular cancer (HCC) in patients with compensated liver cirrhosis (LC) and unaltered liver function. We aimed to evaluate the efficiency and tolerability of lenvatinib in patients with HCC in a real world setting, also including patients with advanced LC and impaired liver function. Methods: Retrospectively, 35 patients with HCC BCLC stages B, C and D were screened. After drop-out and exclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Those reports have been well documented in not only retrospective studies, but also in analyses of the phase-III trials of sorafenib, cabozantinib, ramucirumab, or regorafenib in advanced HCC. [25][26][27][28][29] In the present study, worsening of the ALBI score with atezolizumab plus bevacizumab was observed in both non-e-PD and e-PD patients. In both groups, the ALBI score increased significantly during the first 3 weeks of treatment and did not change thereafter.…”
Section: Patient Characteristicssupporting
confidence: 57%
See 1 more Smart Citation
“…Those reports have been well documented in not only retrospective studies, but also in analyses of the phase-III trials of sorafenib, cabozantinib, ramucirumab, or regorafenib in advanced HCC. [25][26][27][28][29] In the present study, worsening of the ALBI score with atezolizumab plus bevacizumab was observed in both non-e-PD and e-PD patients. In both groups, the ALBI score increased significantly during the first 3 weeks of treatment and did not change thereafter.…”
Section: Patient Characteristicssupporting
confidence: 57%
“…The result is similar to the past reports which showed the prognostic impact of liver function in HCC. Those reports have been well documented in not only retrospective studies, but also in analyses of the phase‐III trials of sorafenib, cabozantinib, ramucirumab, or regorafenib in advanced HCC 25–29 …”
Section: Discussionmentioning
confidence: 93%
“…The study conducted by Cosma et al [7] reported that the differences between the Child-Pugh scores at the beginning and end of therapy were not statistically significant. However, Hatanaka et al [8] reported that the liver function deteriorated from Child-Pugh class A to class B in 43 of the 110 patients (39.1%) following the administration of lenvatinib.…”
Section: Editorialmentioning
confidence: 94%
“…Although a small number of cases were considered in the retrospective study conducted by Komatsu et al [6], there were no significant differences in the pharmacokinetics, safety, and tolerability of lenvatininb between patients with Child-Pugh class B liver function impairment and patients with Child-Pugh class A liver function [6]. In this issue of the Journal of Gastrointestinal and Liver Diseases, retrospective study by Cosma et al [7] revealed that the tolerability and toxicity of lenvatinib were similar between patients with Child-Pugh class A liver function and patients with Child-Pugh class B liver function impairment. The study reported the same results as those obtained by Komatsu et al [6].…”
Section: Editorialmentioning
confidence: 95%
“…Three single-arm real studies [13,15,21] and four comparison studies [22][23][24]26] reported median PFS. In the meta-analysis including single-arm real studies (Fig.…”
Section: Median Pfsmentioning
confidence: 99%